Effect of storage of fresh turmeric rhizomes on oleoresin and curcumin contents - BABU, T JOHN ZACHARIAH, K NIRMAL (Journal of Spices and Aromatic Crops, 1992)
The turmeric varieties Suvarna (PCT·B), Suguna (PCT·13) and Sudarshana (PCT·14), were harvested and stored for a period of nine months. Samples were analysed forcurcumin and oleoresin at monthly intervals. Curcumin and oleoresin levels were not affected by sotrage. The marginal increase in these constitutents after sprouting is only relative as the nutrients like carbohydrates ge t progressively depleted with the progress of sprouting and growth of the sprout. The distribution of curcumin in mother rhizomes and fingers are also discussed.